Pemanfaatan buah campolay (Pouteria campechiana) dalam meningkatkan kualitas wajit cililin - Wikanta, Wiwi; Juniawan, Mulya Fitrah; Mardiyah, Siti (UHAMKA PRESS, 2025)
Wajit Cililin is one of the traditional foods typical of the Cililin Region in West Java. The making of wajit can be varied by adding fruits, such as Campolay Fruit. The use of Campolay Fruit (Pouteria campechiana) in making wajit has never been done before. The purpose of this study was to determine the organoleptic value and nutritional content of Wajit Cililin with the addition of Campolay Fruit (Pouteria campechiana). The study was conducted using an experimental method at the East Java Health Laboratory (Labkesda) and the Medical Laboratory Technology Lab, Muhammadiyah University of Surabaya. Organoleptic data were collected from 20 panelist selected by accidental sampling consisting of men and women aged 17-65 years. Organoleptic and nutritional data were analyzed descriptively. The results showed that panelist really liked the organoleptic in treatment III (wajit with the addition of 200 g Campolay fruit) with an average value of 3.31 (very much like). The nutritional content showed an increase in the addition of 200 g of Campolay Fruit with nutritional values ​​including Calories, Carbohydrates, Fat, Protein, Calcium, β-Carotene, and Vitamin C respectively, namely 262.47 Kcal, 50.62 mg, 5.15 mg, 3.41 mg, 642.85 mg, 1,600 ppm, and 17.5 mg. The results of this study can be concluded that the use of Campolay Fruit (Pouteria campechiana) can improve the quality of Wajit Cililin, both in terms of organoleptic value and nutritional content.